A Shariah-Compliant Model for Urban Development: Langsa Halal Industry and A Hub-City - Munadiati, Munadiati; Kurlillah, Anis; Iskandar, Iskandar; Zulhilmi, Zulhilmi (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2025)
This study explores Kota Langsa, Aceh Province, Indonesia's potential as a halal industry hub-city, addressing gaps in Shariah-compliant urban models. Novelty lies in integrating halal principles with the hub-city concept, grounded in Islamic values of justice, fairness, and sustainability, offering a fresh theoretical framework for Islamic urban economics. Adopting a phenomenological design, in-depth interviews, focus groups, and document analysis were conducted to collect data from the stakeholders. As a result, in the purpose of ensuring halal authenticity, there were significant challenges of inadequate infrastructure, lack of skilled workers, and weak regulations. Responding to the challenges, a five-pillar strategy is proposed: Halal Industry Cluster Development, Infrastructure Enhancement, Human Capital Building, Regulatory Strengthening, and Public-Private Partnerships. This model contributes to Islamic economic theory by showing how to embed ethical practices and social responsibility into urban development. It provides actionable recommendations for policymakers, urban planners, and Islamic finance experts, helping Kota Langsa to drive regional growth by bridging urban development with halal ecosystems.